Finite element analysis and redesign of the telescopic arm of a container spreader - Chia, Gilbert Keng Hoe (Nanyang Technological University, 2012)
This report details systematically the static analysis of the telescopic arm of a container spreader, using the finite element method. The container spreader is a vital component in the transportation of container cargo over short distances, such as from ships to storage facilities at ports and terminals. The telescopic arm structure consists of an end-beam as well as two arm structures. Free vibration analysis was also performed to determine the natural frequency of the structure as well as its mode shapes. It was determined that vibrations at frequencies close to 9.8Hz and 27.3Hz should be avoided.